Inovasi Mie Sehat "SAGULE" (Salmon Guava Leaf) dengan Ekstrak Daun Jambu Biji sebagai Upaya Pencegahan Diare pada Siswa Sekolah Dasar - Mardiana, Mardiana; Yulianto, Yulianto; Sriwiyanti, Sriwiyanti; Tobing, Novita L; Ulfa, Widia; Romadhon, Fajar (Jurnal Pengabdian kepada Masyarakat (ABDIKEMAS), 2025)
Abstract Diarrhea is one of the diseases that often occurs in school-age children, especially due to a lack of awareness of the importance of balanced nutrition. To overcome this problem, a local health-based food innovation was developed, namely Mie Sehat "SAGULE" which uses guava leaf extract and salmon. This product is expected to be able to improve the nutrition of school children and become an affordable alternative to healthy food. This study discusses formulations, production methods, marketing strategies, and their impact on diarrhea prevention. This creativity program in the field of entrepreneurship discusses show that the product "SAGULE" has received a positive response from the target market with the advantage of high nutritional content in the form of protein, omega-3, and antioxidants.